PERAN PENGASUH PONDOK PESANTREN DARUL HIKMAH DALAM MEMBENTUK KARAKTER RELIGIUS MASYARAKAT DESA KALIWEDI KEBASEN BANYUMAS - Khoeriyah, Lulu Latifatul; Nurfuadi, Nurfuadi; Suryatini, Iis (Dirasa Islamiyya: Journal of Islamic Studies, 2022)
Islamic boarding school caretakers are not only responsible for their students, but also for the community. Caretakers also play a role in shaping the religious character of the community. The role of the caretaker is the focus of this study. This study aims to describe how the role of the caretaker of the Darul Hikmah Islamic Boarding School in shaping the religious character of the community. This study were studied to the field directly with the qualitative approach, and serve as a descriptive text. The results showed that the caretaker of the Darul Hikmah Islamic Boarding School has carried out its role as a boarding school caregiver, namely carrying out its role as a teacher, as a parent, as a motivator, as an example, as an advisor, as a trainer for students and the surrounding community so as to be able to shape the religious character of the people of Kaliwedi Village, Kebasen District, Banyumas Regency. to be better in terms of Iman, Islam and ihsan both to fellow humans, fellow creatures, and also to Allah SWT as the essence of the Creator.